The significance of zircon U-Pb ages in the Ba river basin to the timing of major tectonic stages of Kontum massif - Hung, Doan Dinh; Tsutsumi, Yukiyasu; Komatsu, Toshifumi; Hoang, Nguyen; Hung, Nguyen Ba; Ha, Trinh Thai; Dung, Nguyen Thi; Minh, Nguyen Trung (Vietnam Journal of Earth Sciences, 2019)
Ba River originates from the Ngoc Linh mountain ranges, NW of Kontum massif and flows into the East Sea from the Da Rang estuary. The Ba River basin (Da Rang river) is considered as the means of transport and storage of products from the Kontum massif resulted following weathering, erosion or deformation processes either by natural causes or the regional thermo-tectonic events. A total of 122 zircon grains separated from the Ba River basin sediments are selected for U-Pb isotopic age dating by LA-ICP-MS method. Among the 122 samples, 114 are concordant, forming 3 major age groups, including middle-Late Cretaceous (105–85 Ma), Middle Permian - Late Triassic (270–211 Ma), Late Ordovician - Early Silurian (455–424 Ma). A few samples show ages scattering from 1470 to 970 Ma (Mesoproterozoic), and one sample shows a value of 2383±24 Ma (Paleoproterozoic). The acquired U-Pb zircon ages may reflect 3 major thermo- tectonic stages in the formation and evolution of the Kontum Massif from the Early Paleoproterozoic till middle-Late Cretaceous, with the most significant time being Middle Permian (270 Ma)-Late Triassic (211 Ma) (97 over 122 samples, e.g., 79,5%), corresponding to the period of convergence, collision and orogeny of the Indosinian block.